Legality of Western military intervention in Kosovo (1999) - Šavdins, Artūrs (Riga Graduate School of Law, 2018)
The research focuses on the legitimacy of humanitarian interventions. This study analyses the legality of NATO's military intervention in Yugoslavia because it set forth the first precedent of a forced intervention of a group of states without UN authorisation while giving rise to a new legislative practice, namely, the Right to Protect (RtoP). The main goal of the thesis is to examine the criteria for NATO's intervention in Kosovo in terms of their compliance with the norms of international humanitarian law.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; International humanitarian law; Kosovo